Pengembangan Sektor Pariwisata dan Pemberdayaan Masyarakat di Desa Tunggulsari, Kabupaten Pati - Lili Marliyah; Marhaeni Dwi Satyarini; Merli Apriyantika; Tjaturahono Budi Sanjoto; Rini Kusumawardani; Danang Dwi Saputro; Moch Faizal Rachmadi; Jati Wahyu Arisetiawan; Alifta Lutfiaazahra (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Tourism is one of the sectors that plays an important role in foreign exchange earnings and increasing the national economy. Indonesia has a diversity of geographical, demographic and topographic conditions that have great potential in the tourism sector. One of the areas in Indonesia with a myriad of abundant tourism potential is Tunggulsari Village, Pati Regency. This area is a disaster-prone area because it borders directly on the Java Sea. However, the potential of the tourism sector, the expanse of the mangrove area and the fisheries and fisheries sectors make it a potential village. The purpose of this service is to make efforts to develop the tourism sector in Tunggulsari Village in a comprehensive, appropriate, targeted, sustainable and sustainable manner. In addition, community empowerment efforts also aim to improve the quality of human resources. This community service is carried out through methods of socialization, training, application of technology, mentoring and evaluation as well as program sustainability. The results of the service are to increase the competence of human resources massively in collaboration with the local government, conducting various training, counseling, mentoring, socialization and interactive discussions between the service team and partners. In addition, IPTEKS downstream efforts are also given to partners as a form of integrated tourism area development.